2003
DOI: 10.1097/00129492-200311000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Internal Auditory Artery Vasospasm Using Topical Papaverine: An Animal Study

Abstract: Background-Internal auditory artery (IAA) spasm is thought to be one of the causes of postoperative sensory hearing loss after attempted hearing preservation removal of an acoustic neuroma. The use of topical papaverine, a nonspecific vasodilator, to prevent vascular insufficiency to the inner ear and to improve hearing outcomes has been suggested but not proven.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 38 publications
0
26
1
1
Order By: Relevance
“…This change in blood flow may cause impairment in the availability of glucose and oxygen to the cochlea [Brant et al, 1996]. In an animal model (rabbits), topical papaverine prevented mechanically induced vasospasm of the IAA [Morawski et al, 2003].…”
Section: Cvrfs and Their Effect On Inner Ear And Auditory Nerve -Pathmentioning
confidence: 99%
“…This change in blood flow may cause impairment in the availability of glucose and oxygen to the cochlea [Brant et al, 1996]. In an animal model (rabbits), topical papaverine prevented mechanically induced vasospasm of the IAA [Morawski et al, 2003].…”
Section: Cvrfs and Their Effect On Inner Ear And Auditory Nerve -Pathmentioning
confidence: 99%
“…In those ears with a phenomenon of incomplete, or complete lack of, recovery of CBF with subsequent partial or total reduction of DPOAE amplitude at all test frequencies, the corresponding DPOAE phases either increased or demonstrated random scattering. Previous studies have shown similar patterns of partial, reversible CBF recovery suggestive of vasospasm in which DPOAEs responded differently depending on the stimulus frequencies Morawski et al, 2003b). Specifically, lower frequency DPOAEs, though reduced, were generally more robust than those of higher stimulus frequencies.…”
Section: Discussionmentioning
confidence: 56%
“…The subsequent surgical steps for exposing the RW and IAA have been previously described in detail for a protocol developed in this laboratory (Widick et al, 1994;Mom et al, 1999;Morawski et al, 2003b). The first surgical step under visualization via an operating microscope was to expose the cochlea and RW through a post-auricular approach for placement of the LD probe to measure CBF.…”
Section: Animal Experimental Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this, mechanically-induced vasospasm of the internal auditory artery has been demonstrated in a rabbit model (19,20). Several previous studies have reported the occurrence of cerebral vasospasm after surgical removal of various tumors, including acoustic neuroma (7,16,32), left sphenoid wing meningioma (16), posterior fossa ependymoma (12), and skull base tumors Risk factors for cerebral vasospasm have been investigated in numerous previous studies, particularly in the setting of aneurysmal SAH.…”
Section: Discussionmentioning
confidence: 61%